African Chicken Genetic Gains (ACGG) - On Station Data - Dessie, Tadelle; Hamisi Goromela, Ezekiel; Jaramillo, Maria; Bamidele, Oladeji; Adeyinka, Isaac; Sonaiya, Funso; Guangul, Solomon; Kingamkono, Margaret; Bruno, Jasmine; Getachew, Fasil; Adeyinka, Isaac; Komen, Hans; et al. (International Livestock Research Institute, 2023)
A program for accessing, testing, adapting, and catalyzing public-private partnerships for multiplying and making available well-adapted low-input chickens for productivity growth in sub-Saharan Africa. These data may be used to characterize chicken production in the 3 countries of Tanzania, Ethiopia and Nigeria; carry out detailed analysis on chicken production systems, management practices, farmer preferences in the 3 countries, analysis likability data, and determine the productivity and production of select strains under semi-scavenging conditions.This dataset contains the on-station monitoring data for the 3 countries.